A Multistate Analysis of Policyholder Behaviour in Life Insurance—Lasso-Based Modelling Approaches - Lucas Reck; Johannes Schupp; Andreas Reuß (Risks)
Holders of life insurance policies can exercise various options that lead to contract modifications, e.g., full surrender, partial surrender, and paid-up and dynamic premium increase options. Transitions between these contract states materially affect (current and future) cash flows and thus represent a serious source of uncertainty for an insurance company. It is common practice to determine best-estimate assumptions for these transitions independently, i.e., without considering joint determinants of the different aspects of policyholder behaviour. The recent literature also incorporates multistate classical statistical models. Our paper shows how consistent best-estimate transition rates for multiple status transitions can be derived using data science methods. More specifically, we extend existing multivariate approaches based on established statistical models (generalised linear models) with the Lasso method, such that the key drivers for each transition can be identified automatically. We discuss the performance, the complexity and the practical applicability of the different modelling approaches based on data from a European insurer.